2015
DOI: 10.1073/pnas.1507741112
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential impact of an expanded genetic code on protein function

Abstract: With few exceptions, all living organisms encode the same 20 canonical amino acids; however, it remains an open question whether organisms with additional amino acids beyond the common 20 might have an evolutionary advantage. Here, we begin to test that notion by making a large library of mutant enzymes in which 10 structurally distinct noncanonical amino acids were substituted at single sites randomly throughout TEM-1 β-lactamase. A screen for growth on the β-lactam antibiotic cephalexin afforded a unique p-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 56 publications
0
60
0
3
Order By: Relevance
“…One noncanonical amino acid substitution led to an enzyme with increased catalytic efficiency; x-ray crystallographic analysis suggested that the ncAA functioned by restricting the conformation of the active site to more efficiently stabilize the rate-limiting transition state. 298, 299 Similarly, a metA variant was isolated from a random ncAA library using a temperature dependent selection scheme that was stabilized by a keto-containing amino acid by a remarkable 23 °C, and likely involves formation of a ketone adduct to a nucleophilic side chain at the homodimer interface. Similar in vitro evolution experiments have demonstrated that ncAAs with long chain thiols can form extended disulfide crosslinks that lead to significant protein stabilization.…”
Section: Applications Of Non-canonical Amino Acidsmentioning
confidence: 99%
“…One noncanonical amino acid substitution led to an enzyme with increased catalytic efficiency; x-ray crystallographic analysis suggested that the ncAA functioned by restricting the conformation of the active site to more efficiently stabilize the rate-limiting transition state. 298, 299 Similarly, a metA variant was isolated from a random ncAA library using a temperature dependent selection scheme that was stabilized by a keto-containing amino acid by a remarkable 23 °C, and likely involves formation of a ketone adduct to a nucleophilic side chain at the homodimer interface. Similar in vitro evolution experiments have demonstrated that ncAAs with long chain thiols can form extended disulfide crosslinks that lead to significant protein stabilization.…”
Section: Applications Of Non-canonical Amino Acidsmentioning
confidence: 99%
“…For example, replacing valine-216 in b-lactamase with p-acrylamido-phenylalanine (13) improved its catalytic efficiency eightfold [47]. None of the twenty natural amino acids conferred a similar enhancement, underlining the unique potential of UAAs in protein engineering and directed evolution.…”
Section: Enzyme Mechanisms and Protein Engineeringmentioning
confidence: 99%
“…For example, it has been recently shown that a unique noncanonical amino acid mutation in TEM-1 β-lactamase significantly increases the enzyme's catalytic activity for the substrate cephalexin, a result that cannot be recapitulated by substitution of canonical amino acids at this site (1). This same enzyme has been reengineered to be dependent on a noncanonical active site residue for activity, a dependency that was maintained for hundreds of generations without escape (2).…”
mentioning
confidence: 99%